2019
DOI: 10.3389/fpubh.2018.00387
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of Health-Related Behavior Patterns and Demographics. Results From the Population-Based KORA S4/F4 Cohort Study

Abstract: Background: Health behaviors are of great importance for public health. Previous research shows that health behaviors are clustered and do not occur by chance. The main objective of this study was to investigate and describe the clustering of alcohol consumption, nutrition, physical activity and smoking while also considering the influence of sex, age and education.Methods: Using data from the population-based KORA S4/F4 cohort study, latent class regression analysis was undertaken to identify different cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 52 publications
2
31
0
1
Order By: Relevance
“…Life-style behaviours are the most crucial determinant [ 5 , 6 ] and lie at the root of many chronic diseases [ 7 14 ] causing higher disease burden [ 15 ] and premature mortality worldwide [ 16 , 17 ]. There is evidence that lifestyle risk factors like tobacco smoking and chewing, alcohol consumption, unhealthy diet are associated and tend to co-occur [ 8 , 18 , 19 ] as clusters [ 9 , 10 , 20 ] or in bundles [ 6 ]. Evidence suggests that population that indulge in multiple health risk factors tend to have significantly worse health outcomes than those engaging in one health risk behaviour [ 15 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Life-style behaviours are the most crucial determinant [ 5 , 6 ] and lie at the root of many chronic diseases [ 7 14 ] causing higher disease burden [ 15 ] and premature mortality worldwide [ 16 , 17 ]. There is evidence that lifestyle risk factors like tobacco smoking and chewing, alcohol consumption, unhealthy diet are associated and tend to co-occur [ 8 , 18 , 19 ] as clusters [ 9 , 10 , 20 ] or in bundles [ 6 ]. Evidence suggests that population that indulge in multiple health risk factors tend to have significantly worse health outcomes than those engaging in one health risk behaviour [ 15 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The only exception was physical activity; the higher percentage of men was active in comparison to women (17) . Although it has been well established that men are more likely to engage in unhealthy behaviours than women (18)(19)(20) , there is a gap in the understanding of which particular dietary behaviours tend to cluster with other lifestyle behaviours. Only a few studies reported clusters of dietary and lifestyle behaviours specific to the population of young men (21) , despite strong recommendations to analyse behavioural patterns using age and gender stratification (22) .…”
mentioning
confidence: 99%
“…We found that cumulative ETV was associated with latent profiles of multiple risk behaviors implicated in developing chronic diseases, premature mortality, and health disparities. 4,9,10 We found 4 distinct latent profiles: low overall risk profile , physically inactive profile, high substance use profile, and high overall risk profile . Notably, individuals with high ETV were more likely to be in the high overall risk profile with high levels of alcohol and cigarette use, unhealthy diet, and increased physical inactivity.…”
Section: Discussionmentioning
confidence: 78%
“…They found being male and having lower SES were associated with the prevalence of unhealthy behavioral clusters. 3,9 -11 Nevertheless, one cross-sectional study focusing on multiple risk behaviors among African Americans found that social-environmental factors (e.g., perceived neighborhood cohesion), compared to demographic or individual-level psychological factors (e.g., perceived cancer risk), plays a much more critical role in differentiating the healthiest group from groups engaging in less healthy behaviors. 8 In line with this finding, researchers have also found that exposure to violence (ETV) influences health outcomes.…”
Section: Purposementioning
confidence: 99%